2021
DOI: 10.1186/s12886-021-01920-8
|View full text |Cite|
|
Sign up to set email alerts
|

Panretinal photocoagulation after or prior to intravitreal conbercept injection for diabetic macular edema: a retrospective study

Abstract: Background Panretinal photocoagulation treatment (PRP) have been known as a standard treatment for proliferative diabetic retinopathy (PDR) or severe nonproliferative diabetic retinopathy (sNPDR). However, there is no consensus on when PRP should be administrated if anti-VEGF treatment is needed for the concurrent diabetic macular edema (DME). This study is to evaluate the difference between two groups of PRP prior to, or after intravitreal conbercept (IVC) for patients with PDR or sNPDR combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Conbercept can block the activation of VEGF and SDF-1 receptors by binding to the receptors of VEGF and SDF-1, prevent the expression of VEGF and SDF-1 in cells, and indirectly reduce the expression of IL-6 [ 27 ]. Eventually, it reduces the expression of VEGF, SDF-1, and IL-6, inhibits endothelial cell proliferation and angiogenesis, and prevents increased foveal thickness and increased macular partial size in patients [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conbercept can block the activation of VEGF and SDF-1 receptors by binding to the receptors of VEGF and SDF-1, prevent the expression of VEGF and SDF-1 in cells, and indirectly reduce the expression of IL-6 [ 27 ]. Eventually, it reduces the expression of VEGF, SDF-1, and IL-6, inhibits endothelial cell proliferation and angiogenesis, and prevents increased foveal thickness and increased macular partial size in patients [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al reported that there was no significant difference in change of BCVA and CMT between IVC before and after PRP group. For IVC after PRP therapy, the result of subgroup analysis in our study showed that eyes received PRP combined with earlier (≤ 1 month) or later (> 1 month) anti-VEGF therapy were also no significant difference for outcomes [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the data before and after the four treatment periods revealed that laser photocoagulation combined with conbercept injection had a better treatment effect on DME, which can effectively improve the visual quality of patients and inhibit retinal thickening[ 21 ]. Retinal laser photocoagulation reduces macular edema in the following two ways: One is by blocking the capillary network through the thermal effect of the laser, which decreases the permeability of the retina and reduces the infiltration rate; and other is in the retinal epithelium that damages the photoreceptor cells in the retina and decreases their VEGF expression, which decreases angiogenesis in the retina and improves its hypoxic state.…”
Section: Discussionmentioning
confidence: 99%